Whole-body protein turnover in malnourished patients with child class B and C cirrhosis on diets low to high in protein energy - Dichi, J. B.; Dichi, I; Maio, R.; Corrêa, Camila Renata [UNESP]; Angeleli, AYO; Bicudo, M. H.; Rezende, T. A.; Burini, Roberto Carlos [UNESP] (Elsevier B.V., 2001)
The purpose of this study was to determine the rate of whole-body protein turnover in moderately and severely alcoholic, malnourished, cirrhotic patients fed with different amounts of protein or energy. Six male patients (Child classes B and C) and four age- and sex-matched healthy control subjects were studied for 18 d in fasting and feeding states; a single oral dose of [N-15]glycine was used as a tracer and urinary ammonia was the end product. The kinetic study showed that patients had higher protein catabolism while fasting (patients: 3.14 +/- 1.2 g of lean body mass/9 h; controls: 1.8 +/- 0.3 g of lean body mass/9 h: P<0.02). Although not statistically significant, protein catabolism (grams of lean body mass/9 h) was lower with the hyperproreic/hyperenergetic diet when compared with fasting. Nitrogen retention was consistent with the lower protein-catabolism rate; a statistically significant increase in nitrogen balance was observed when patients were fed with the hyperproteic/hyperenergetic diet compared with fasting 14.3 +/- 3.2 g of nitrogen/d and -2.2 +/- 1.9 g of nitrogen/d, respectively; P < 0.01). These data indicate that Child class B and C cirrhotic patients are hypercatabolic and that Long-term nutritional intervention with a hyperproteic/hyperenergetic diet is likely needed to improve their clinical and nutritional status. Nutrition 2001;17:239-242. (C) Elsevier B.V. 2001.
Keywords: liver cirrhosis; nutrition; protein metabolism; diet